2014
DOI: 10.1002/ldr.2296
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Organic Amendments on Forest Soil Properties Under Mediterranean Climatic Conditions

Abstract: Restoring the native vegetation is one of the most effective ways to control soil degradation in Mediterranean areas, especially in very degraded areas. In the initial months after afforestation, vegetation cover establishment and soil quality could be better sustained if the soil was amended with an external extra source of organic matter. The goal of this study was to test the effect of various organic amendments on select soil properties [soil organic carbon (SOC), pH, and electrical conductivity (EC)] over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 60 publications
4
64
0
6
Order By: Relevance
“…However, in the performed study, the explorations starting point were parcels that were already under the extensive forage system of exploitation and the farmers only adhered to these measures given the economic support that would come to them. In this case, and as demonstrated in the study of [57], the organic carbon content changes very slowly and even slower as the system tends to equilibrium.…”
Section: Organic Carbonsupporting
confidence: 54%
“…However, in the performed study, the explorations starting point were parcels that were already under the extensive forage system of exploitation and the farmers only adhered to these measures given the economic support that would come to them. In this case, and as demonstrated in the study of [57], the organic carbon content changes very slowly and even slower as the system tends to equilibrium.…”
Section: Organic Carbonsupporting
confidence: 54%
“…assessed the value of organic amendments on vegetation establishment and soil fertility, as for contaminated areas (Mahmoud and Abd El-Kader, 2015), post-mine soils (Eldridge et al, 2012;Benigno et al, 2013), semi-arid conditions (Hueso-González et al, 2014;Jiménez et al, 2013;Tejada and Benítez, 2014) and eroded soils (Ojeda et al, 2003;Cohen-Fernández and Naeth, 2013;Prats et al, 2013;Hosseini Bai et al, 2014;Donn et al, 2014;Hueso-González et al, 2015). Others have also shown the direct effect of organic mulch in reducing surface runoff (Moreno-Ramón et al, 2014;Cerda et al, 2015;Sadeghi et al, 2015).…”
Section: Breton Et Al: Effects Of Wood Chip Amendments On the Revmentioning
confidence: 99%
“…Incorporating sludge into soil will increase the fertility of soil and stimulate growth of certain groups of bacteria and fungi as well as improve aggregation of the soil. According to listed reports, sludge amendment, to some extent, improve biochemical and physical properties of the soil (Hueso- Gonzalez et al, 2014;Joniec and Kwiatkowska, 2014;Mingorance et al, 2014). Beside these functions mentioned above, there is a not accustomed role to be understood in relationship between organic matter and heavy metal.…”
Section: Organic Matter Plays Crucial Role In Availability Of Heavy Mmentioning
confidence: 99%
“…Hueso- Gonzalez et al (2014) drew a conclusion that sludge increased the electrical conductivity in amended soil. Surampalli et al (2008) reported that amending too much sludge to soil over a ten year period could occasionally cause groundwater to become contaminated with nitrates.…”
Section: Organic Matter Plays Crucial Role In Availability Of Heavy Mmentioning
confidence: 99%